The sublime in the homopoetic of Vicente Aleixandre - Campos López, Ronald (2017)
This article aims to develop a “des-concealment” work of the “homopoetics” of Vicente Aleixandre. For this, symbols, visions and visionary images are analyzed as expressions of a homoeroticism, where sublime experiences predominate and define to the lyrical homosexual lovers and the cosmic, contextual and intimate environment. The poems “Se querían”, “Mano entregada” and “No busques, no” are interpreted into a hermeneutical reading. This concludes that the sublime significantly participates in the consolidation of Aleixandre’s “homopoetics” in two ways. Firstly, the sublime is manifested as an attempt to convert daily homoerotic elements and experiences into something that elevates and transforms the lyrical subject through imagination. Secondly, the sublime defines, as “homotexting” resources, the play with light and shadow, the ambiguity, the hermetic, the splitting, the macro-cosmic and micro-cosmic limits, the blood symbolisms, the surrealist visionary images, the phenomenological and imaginative visions, an ecological awareness, the synesthesia generating, the homoerotic identity and confessions fragmentation, the antiphrasis and the litotes.